Ո՞վ է Սուրբ Ոսկյանց և Սուրբ Սուքիասյանց վկայաբանություններում հիշված Հայոց Արտաշես թագավորը, և ովքե՞ր՝ նրա որդիները - Անտոնյան, Անահիտ (Մայր Աթոռոյ Սրբոյ Էջմիածնի)
Совокупность агиографических данных, сообщений армянских историков и греко-римских источников свидетельствует о том, что известного в армянской исторической литературе и агиологии царя Арташеса (Арташеса II, согласно армянским историкам) не следует отождествлять с царем Арташесом I, правившим в Армении в II в. до н.э., как признает историография, но с Вагаршем I, правившим в I—II вв. Свидетельства о св. Воскянк и св. Сукиасянк ценились как самостоятельный источник, написанный до V века, т. е. появления армянского алфавита. Новая интерпретация сведений показывает, что данные армянской литературы о царе Арташесе и его сыновьях не противоречат сообщениям зарубежных источников: они сопоставимы, и нет необходимости использовать армянские сведения с гипотетическим переосмыслением, перемещая исторические фигуры и события во времени. A combination of hagiographic data, reports of Armenian historians and Greco- Roman sources suggests that King Artashes (Artashes II, according to Armenian historians), known in Armenian historical literature and hagiology, should not be identified with King Artashes I that ruled in Armenia in the 2nd century BC, as acknowledged by historiography, but with Vagharsh I, who ruled in the 1st—2nd centuries AD. The martyrologies of Sts. Voskyank and St. Sukiasyank were valued as an independent source, written before the 5th century, i.e. the emergence of the Armenian alphabet. The new interpretation of the information shows that the data of the Armenian literature about King Artashes and his sons does not contradict the reports of foreign sources: they are comparable, and there is no need to use the Armenian information with a hypothetical reinterpretation, moving historical figures and events in time.
Keywords: Կրօնագիտութիւն